Desenvolvimento do sistema de rastreamento de um protótipo de concentrador solar fresnel linear - Negreiros, Igor Soares (2015)
Amid the great crisis of the energy, new methods for electric power generation, especially those do not harm the environment, are constantly sought to meet the growing need worldwide. Among them, the use of Fresnel linear concentrators becomes increasingly feasible, due to have lower cost in comparison to other types of solar concentrators. Thus, the project seeks to develop techniques that optimize use of the system where the main objective is to implement and validate the tracking system for a prototype of linear Fresnel solar concentrator, operating between approximately 7:30 and 16:30 in Fortaleza, Ceará. For that, it used microcontrollers, sensors and motors to design a system capable of tracking Solar light system. The characterization and validation of the inductive position sensor used is also an important part of the work. To perform the tracking system, have been used a theoretical methodology for relative location of the sun, beyond the gain scheduling technique in control of employee movement. The position sensor validation have a maximum error than 0.3º. Therefore, can consider that, with the use of the techniques employed for the achievement of system of control, the medium error obtained was about 0.06°, making the design perform the concentration of solar rays in the absorber concentrator with a maximum deviation of 0.5°, providing the desired reliability for system use